Lower‐risk myelodysplastic syndromes: Current treatment options for anemia. Issue 4 (12th August 2022) - Meunier, Mathieu; Park, Sophie
Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal hematological disorders. Treatment options are classified and defined by prognostic risk based on the International Prognostic Scoring System (IPSS) and, more recently, the revised IPSS (IPSS‐R). The treatment goal for lower‐risk MDS is to correct cytopenias or their consequences, with the goal of maintaining or improving quality of life. Erythropoiesis‐stimulating agents (ESAs) play an important role in treating anemia. Individuals with MDS who have a 5q deletion are particularly sensitive to treatment with lenalidomide; however, this comprises the minority of patients with MDS. Luspatercept was recently approved in the United States and the European Union for the treatment of ESA‐refractory MDS with ring sideroblasts. Research into new treatment options, especially after ESA failure, is needed. In this review, we will focus on the current therapeutic options for MDS‐related anemia.